GE_GERICHTE C/9096/2014 vom 5. November 2012 - GE Cour de justice (2012)
MANDAT; CURATEUR; CURATELLE DE GESTION(ANCIEN ART. 393 CC); CURATELLE DE REPRÉSENTATION(ART. 394 CC); PROPORTIONNALITÉ | CC.394; CC.395; CC.390; CC.423; CC.400